1988
DOI: 10.1093/oxfordjournals.rpd.a080256
|View full text |Cite
|
Sign up to set email alerts
|

Uranium in Humans

Abstract: Measurements of the environmental and metabolic behaviour of the naturally occurring radionuclides have provided necessary information on the behaviour of stable elements and have been useful analogues in the study of man-made radionuclides. Uranium has been studied primarily because of its role in the nuclear industry and its possible effects as a heavy metal in occupational exposure cases. There is abundant literature dealing with uranium studies in animals, and some literature on human studies with chronica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34]. This finding is in agreement with those of other researchers [32,35]. The degrees of accumulation of uranium in the tissues (kidney, breast, stomach, and uterus) are ranked as follows: kidney [ stomach [ breast [ uterus for normal and abnormal tissues.…”
Section: Resultssupporting
confidence: 87%
“…From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34]. This finding is in agreement with those of other researchers [32,35]. The degrees of accumulation of uranium in the tissues (kidney, breast, stomach, and uterus) are ranked as follows: kidney [ stomach [ breast [ uterus for normal and abnormal tissues.…”
Section: Resultssupporting
confidence: 87%
“…The human body contains approximately 56 μg of U; 32 μg (56%) in the skeleton, 11 μg in muscle tissue, 9 μg in fat, 2 μg in blood and less than 1 μg in the lungs, liver and kidneys (Fisenne et al 1988). Kidneys are considered to be the most sensitive target organ for chemical toxicity of U and long-term ingestion of the element by humans leads to progressive kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Die wei te re Bi lan zie rung er gibt für Muskel ge we be 20, Fett ge we be 15, Blut 4 und für Lun ge, Le ber und Nie re etwa 1-2 [23].…”
Section: Bio Ki Ne Tik Des Ur Ansunclassified